A study on the adequacy of peaceful assembly act 2012 in Malaysia / Nur Arina Abdul Hadi, Nur Syafina Munirah Mohd Nasir and Nurul Izza Shamsul Kamal - Abdul Hadi, Nur Arina; Mohd Nasir, Nur Syafina Munirah; Shamsul Kamal, Nurul Izza (Faculty of Law, 2012)
The right to assemble is one of the fundamental liberties guaranteed by the Federal Constitution under Article 10. This right ensures that all citizens are allowed to organize and participate in an assembly. Ever since this right has been conferred to the people, some limitations have been provided by the law to control the exercise of this right. However, the current situation in our country where lots of illegal assembly were carried out by various groups of individuals demanded the right to assembly to be reviewed by the government through the parliament. This is due to the fact that more and more people are resorting to illegal assemblies whenever they want to voice out their grievances and opinions. Consequently, some of the assemblies conducted caused public discomfort and disorder. As a result of this, government finds it necessary to pass a law to regulate and govern the right to assembly to meet the current situation in the country. Thus, in November 2011, the parliament passed the Peaceful Assembly Act which came into force in April 2012. This Act is actually a replacement for section 27 of Police Act 1967 which has been repealed on 31st August 2011. The passing of this new Act draws the attention of the public as well as local and international organizations. Lots of critics have been received from various individuals, groups and organization which among others, alleged that the Act is draconian and oppressive. Despite of the critics, the Act, at the same time, also received lots of credits as it has been passed at the time when the country needed it the most. This research paper aims to draw the attention on the flaws being purported against this Act and provides some recommendations to overcome the alleged flaws as claimed by some people. Among the issues that will be discussed in this research paper include, the purpose of this Act, the compliance of this Act with the right to assembly under the Federal Constitution, prohibition on assembly to certain groups of individuals, the wide power of the police as well as the comparison with other similar Act in the United Kingdom. We hope that this research paper will be a reading that will provide a better understanding on this Act and at the same time be able to correct people's perception on this Act.